Transactions on Engineering Technologies International MultiConference of Engineers and Computer Scientists 2017 - Ao, Sio-Iong.; Kim, Haeng Kon.; Castillo, Oscar; Chan, Alan Hoi-Shou.; Katagiri, Hideki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume contains a selection of revised and extended research articles written by prominent researchers participating in the 25th International MultiConference of Engineers and Computer Scientists (IMECS 2017) which was held in Hong Kong, 15-17 March, 2017. Topics covered include electrical engineering, communications systems, engineering mathematics, engineering physics, and industrial applications. With contributions carefully chosen to represent the most cutting-edge research presented during the conference, the book offers the state of art in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.
1 transportation safety improvements through video analysis: an application of obstacles and collision detection applied to railways and roads -- 2 it-security concept cornerstones in industrie 4.0 -- 3 further in-depth investigation of precuing effect on tracking and discrete dual-task -- 4 improvement of maximum production in the batch transesterification reactor of biodiesel by using nonlinear model based control -- 5 production scheduling tools to prevent and repair disruptions in MRCPSP -- 6 a supply chain design of perishable products under uncertainty -- 7 the relationships between education level, income level and prior experience, and the attitude of college students about online shopping in hong kong -- 8 risk mitigation strategy for public private partnership (ppp) of airport infrastructure development in indonesia -- 9 an experimental study of adhesion between aggregate minerals and asphalt binders using particle probe scanning force microscopy -- 10 approaches to a descent underwater vehicle stabilization in conditions of a sea disturbance -- 11 a comparison of different quasi-newton acceleration methods for partitioned multi-physics codes -- 12 implementation of international safety standard en iso 13849 into machinery of tyre industry -- 13 investigation on bidirectional dc/dc converters for energy management and control -- 14 distributed lock relation for scalable-delay-insensitive circuit implementation based on signaltransition graph specification -- 15 a neural network based soft sensors scheme for spark-ignitions engines -- 16 a tourist spot search system based on paragraph vector model of location and category tags using user reviews -- 17 learning method of fuzzy inference systems for secure multiparty computation -- 18 solving the fagnano's problem via a dynamic geometry approach -- 19 an innovative approach to video based monitoring system for independent living elderly people -- 20 color blindness image segmentation using rho-theta space -- 21 estimation ofglobal image threshold based on statistical change-point detection -- 22 automated computer vision system based on color concentration and level for product quality inspection -- 23 applied finite automata and quadtree technique for thai sign language translation -- 24 improvement method for topic-based path model by using word2vec -- 25 how to find similar users in order to develop a cosmetics recommender system -- 26 applied finite automata and quadtree technique for thai sign language translation -- 27 historical event-based story creation support system for fostering historical thinking skill -- 28 japanese-chinese cross-language entity linking adapting to user's language ability.
Keywords: Industrial engineering; Production engineering; Electrical engineering; Application software; Computational intelligence; Data mining; Industrial and Production Engineering; Electrical and Electronic Engineering; Computer and Information Systems Applications; Computational Intelligence; Data Mining and Knowledge Discovery